Less sclerotic microarchitecture pattern with increased bone resorption in glucocorticoid-associated osteonecrosis of femoral head as compared to alcohol-associated osteonecrosis of femoral head - Chen, Yiwei; Miao, Yu; Liu, Kexin; Zhu, Bin; Xue, Feng; Yin, Junhui; Zou, Jian; Li, Guangyi; Zhang, Changqing; Feng, Yong (Frontiers in Endocrinology, 2023)
Background: Glucocorticoid usage and alcohol abuse are the most widely accepted risk factors for nontraumatic osteonecrosis of femoral head (ONFH). Despite distinct etiologies between glucocorticoid-associated ONFH (GONFH) and alcohol-associated ONFH (AONFH), little is known about the differences of the microarchitectural and histomorphologic characteristics between these subtypes of ONFH. Purposes: To investigate bone microarchitecture, bone remodeling activity and histomorphology characteristics of different regions in femoral heads between GONFH and AONFH. Methods: From September 2015 to October 2020, 85 patients diagnosed with GONFH and AONFH were recruited. Femoral heads were obtained after total hip replacement. Femoral head specimens were obtained from 42 patients (50 hips) with GONFH and 43 patients (50 hips) with AONFH. Micro-CT was applied to evaluate the microstructure of 9 regions of interest (ROIs) in the femoral head. Along the supero-inferior orientation, the femoral head was divided into necrotic region, reactive interface, and normal region; along the medio-lateral orientation, the femoral head was divided into medial region, central region and lateral region. Decalcified and undecalcified bone histology were then performed to assess histopathological alterations and bone remodeling levels. Results: In the necrotic region, most of the microarchitectural parameters did not differ significantly between GONFH and AONFH, whereas both the reactive interface and normal region exhibited a less sclerotic microarchitecture but a higher bone remodeling level in GONFH as compared with AONFH. Despite similar necrotic pathological manifestations, subchondral trabecular microfracture in the necrotic region was more severe and vasculature of the reactive interface was more abundant in GONFH. Conclusions: GONFH and AONFH shared similar microarchitecture and histopathological features in the necrotic region, while GONFH exhibited a less sclerotic microarchitecture and a more active bone metabolic status in both the reactive interface and normal region. These differences between GONFH and AONFH in bone microarchitectural and histopathological characteristics might contribute to the development of disease-modifying prevention strategies and therapeutics for ONFH, taking into etiologies. Keywords: Osteonecrosis of the femoral head; glucocorticoid; alcohol; micro-computed tomography; bone microstructure; bone histopathology; bone remodeling